‘Alpha-mädchen sind wir alle’ [we’re all alpha girls]: subjectivity and agency in contemporary pop-feminist writing in the US, Britain and Germany - Spiers, E (2014)
This thesis investigates models of subjectivity and agency in early twenty-first-century pop-feminist fiction and non-fiction. Non-fiction accounts of subjectivity (Haaf, Klingner and Streidl, 2008; Valenti, 2007; Moran, 2011 et al.) draw on poststructuralist notions of incoherent, performative identity, yet retain the assumption that there remains a sovereign subject capable of claiming full autonomy. The pop-feminist non-fictions reflect a neoliberal model of entrepreneurial individualism where self-optimisation replaces an ethics of intersubjective relations. In exploring the theoretical blind-spots of pop-feminist claims to female autonomy and agency, this thesis sets out to demonstrate that pop-feminist non-fiction lacks an actual feminist politics. My methodology is comparative and primarily involves the close reading of a corpus of pop-feminist texts from the Anglo-American and German contexts. I utilize my corpus of current essayistic pop-feminist texts as a fixed point of reference, deeming them to be representative of a pervasive kind of contemporary postfeminist thinking. Through the employment of the first-person narrative voice the literary authors explore how subjects are constituted by discourse but also how the subject may shape her choices/actions. Subjectivity becomes a generative capacity characterised by expansive and self-reflexive negotiations between self and other. The fictional portrayal of this process prompts an imaginative and extrapolative process of identification and dis-identification in the reader which opens up a site for the exercise of critique. Through my close readings of the novels (Riley, 2002; Walsh, 2004; Thomas, 2004; Grether, 2006; Roche, 2008; Bronsky, 2008; Baum, 2011; Hegemann, 2010) I develop a model of intersubjective dependency, drawing on Judith Butler’s later work (1994, 1999, and 2005), and identify versions of this model in the 1980s-1990s work of American postmodern feminist writers Kathy Acker and Mary Gaitskill. My thesis reveals hitherto un-discussed lines of literary and critical influence on the contemporary British and German novelists emanating from Acker and Gaitskill, suggesting that their texts may be viewed as representative of a critical pop-literary interest, spanning approximately three decades and shifting across cultural contexts, in the encounter between female subjectivity and agency in the face of late-capitalist manifestations of social constraint.